2021
DOI: 10.1016/j.stemcr.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH-mediated ex vivo expansion of human hematopoietic stem and progenitor cells by culture under hypoxia

Abstract: Summary Activation of NOTCH signaling in human hematopoietic stem/progenitor cells (HSPCs) by treatment with an engineered Delta-like ligand (DELTA1 ext-IgG [DXI]) has enabled ex vivo expansion of short-term HSPCs, but the effect on long-term repopulating hematopoietic stem cells (LTR-HSCs) remains uncertain. Here, we demonstrate that ex vivo culture of human adult HSPCs with DXI under low oxygen tension limits ER stress in LTR-HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The hypoxic condition also supports the stability of HIF-2α heterodimerization with HIF-1β. Since unbound HIF-1β under normoxia binds to aryl hydrocarbon receptor (AhR) that triggers transcription of cellular differentiation genes CYP1A1 and CYP1B1, confirming the crucial role of AhR pathway in self-renewal ( Araki et al, 2021 ). AhR antagonists like Stem-Reginin1 (SR1) can increase the HSCs numbers by 50-fold and establish long-term engraftment in immunodeficient mice ( Boitano et al, 2010 ).…”
Section: Regulating Hematopoietic Stem Cells For Clinical Usementioning
confidence: 88%
See 2 more Smart Citations
“…The hypoxic condition also supports the stability of HIF-2α heterodimerization with HIF-1β. Since unbound HIF-1β under normoxia binds to aryl hydrocarbon receptor (AhR) that triggers transcription of cellular differentiation genes CYP1A1 and CYP1B1, confirming the crucial role of AhR pathway in self-renewal ( Araki et al, 2021 ). AhR antagonists like Stem-Reginin1 (SR1) can increase the HSCs numbers by 50-fold and establish long-term engraftment in immunodeficient mice ( Boitano et al, 2010 ).…”
Section: Regulating Hematopoietic Stem Cells For Clinical Usementioning
confidence: 88%
“…One method to go about it is by Notch signalling activation within HSCs. Treating HSCs with an engineered Delta-like ligand like DELTA1 ext−IgG (DXI) under normoxic conditions activates the Notch pathway in ST-HSCs by triggering the transcriptional activity of HES and HEY genes responsible for self-renewal ( Araki et al, 2021 ). However, this engraftment did not sustain for long since it was ineffective on the LT-HSCs.…”
Section: Regulating Hematopoietic Stem Cells For Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of BA-regulated ER stress signaling in HSCs is further supported by seminal works from the Miharada lab which demonstrated that fetal HSCs exhibit low levels of adaptive responses to ER stress that significantly depend on BA chaperone activity for expansion and differentiation [203,204]. As such, the involvement of ER stress signaling in HSC homeostasis is gaining momentum in research, as seen in several new reports on this topic [205][206][207][208][209]. Importantly, the mechanism that allows ENT3 to regulate erythroid pool size introduces a new concept into the understanding of stress-adaptive ER stress signaling in HSCs [207].…”
Section: A Role For Nucleoside Transporters In Mammalian Hematopoiesismentioning
confidence: 91%
“…The Notch signaling pathway can be proved to mediate the differentiation of HSCs. It has been found that Notch1 can facilitate T-cell differentiation and inhibit B-cell differentiation [ 37 ]. Notch2 signaling affects HSC self-renewal by inhibiting the differentiation of HSCs to multipotent progenitors (MPP) and MPP differentiation to myeloid/monocytic (M) cell lineage [ 16 ].…”
Section: Ex Vivo Expansion Of Hscsmentioning
confidence: 99%